Permainan Olahraga Terhadap Perkembangan Fisik dan Motorik Anak - Meriani Meriani; Herlina Herlina; Herman Herman; Wahira Wahira; Darwis, Assidiq (KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the physical and motor development abilities of children in the control and experimental groups before and after treatment in the study on the influence of sports games. This study uses a quasi-experimental method. The research design is a Nonequivalent Control Group Design with two groups: the experimental group receiving treatment and the control group not receiving treatment. The data collection technique uses observation, testing, and documentation. The data analysis used a t-test. The results showed that the physical and motor development abilities of the group B children in the control group before treatment were generally moderate to high. In the experimental group B, the initial ability before treatment was similar to that of the control group, with basic gross motor potential (82%+) but limited agility. After being given the sports game treatment, there was a marked improvement to a high level (87%+), especially in muscle strength, balance, and hand-eye coordination, proving the effectiveness of the intervention., there was a significant difference in the physical and motor development of the children of group B between the experimental group that participated in the sports game and the control group that did not, where the experimental group showed superior progress on all motor indicators—confirming the positive influence of sports games on early childhood development. Early childhood teachers are advised to integrate simple sports games such as jumping rope, throwing balls, or obstacle courses at least 3 times a week for 30 minutes for gross and fine motor optimization. Schools need to provide safe facilities such as mini courts and playgrounds with early age standards, as well as train teachers through workshops for fun game variations.